THE STUDY OF NON-EQUIVALENT VOCABULARY AND REALIA IN THE CONTEXT OF CONTEMPORARY GERMAN LINGUISTIC RESEARCH - Eshmuradov Ural Khujanovich (Bright Mind Publishing, 2025)
The paper also examines the influence of socio-cultural, historical, and technological contexts on the formation of non-equivalent vocabulary and the strategies used by translators to overcome these barriers. Through analysis of German vocabulary in literary, business, and cultural texts, this study demonstrates that effective translation requires not only linguistic expertise but also cultural knowledge, intuition, and strategic adaptation. Understanding these phenomena is crucial for enhancing both the accuracy and cultural fidelity of translations.
Keywords: realia, non-equivalent vocabulary, translation strategies, cultural linguistics, equivalence, temporarily non-equivalent terms